Perdas de solo e água em lavouras sob plantio direto com e sem terraceamento agrícola - Bisolo, Alinne (2025)
The intensification of agricultural practices and changes in soil management methods have led to the need to understand and quantify the impacts generated by anthropogenic interactions in order to contribute to hydrosedimentological knowledge in rural areas. This study aims to quantify soil and water losses in crops under a notillage system, with and without the presence of agricultural terraces. The study was carried out in 1.92 ha of farmland in the experimental area of the Federal Technological University of Paraná – Dois Vizinhos Campus, in the southwest of Paraná. The variables of precipitation, flow and sediment production were evaluated from a total of 20 events in terraced crops and 28 events in non-terraced crops during the period from August 2022 to December 2023, with the occurrence of the El Niño meteorological phenomenon from June 2023, where the highest precipitations were recorded in the months of October 2022, with 516.4 mm per month and October and November 2023, with monthly precipitations of 631.8 and 309.6 mm, respectively. The largest event in terms of duration occurred on October 28 and 29, 2023, lasting 36 hours, and the largest volume of water and soil lost occurred on November 3 of the same year, with 179.96 m³ of water and 8.36 kg of soil lost in the terraced crop and 339.94 m³ and 34.29 kg in the non-terraced crop, respectively. The results showed that the nonterraced crop tended to have higher proportions of water and soil loss compared to the terraced crop. The total soil loss during the period of this study was 20.30 kg in the terraced crop and 119.08 kg in the non-terraced crop. The total water loss was 467.70 m³ in the area with terraces and 1,186.47 m³ in the area without terraces, which represents a reduction of 82.9% in soil losses and 60.7% in water losses in the system with agricultural terraces. High magnitude events were responsible for the largest fraction of soil and water losses that occurred during the study period, considering the total number of monitored events, which reinforces the need for mechanical practices to control surface runoff in direct planting areas.